Study on circumpelvic muscle deformation and dynamic simulation of pelvic fracture reduction. Issue 6 (26th April 2023) - Lei, Jingtao; Li, Yanan; Xu, Haifei
Abstract: For the pelvic fracture reduction, generally the fragment of the unaffected side is fixed and the affected side is moved to its correct anatomical position and orientation. During the pelvic fracture reduction, circumpelvic muscles deformation is closely related to the surgical accuracy. In this article, the biomechanical properties of musculoskeletal tissue during pelvic fracture reduction are studied. Five-parameter hyperelastic model named Mooney-Rivlin is adopted to analyze muscle's stress–strain relationship. The finite element model of the injured pelvic musculoskeletal tissue is established, and the deformation of circumpelvic main muscles is simulated. Then, the dynamic simulation of pelvic fracture reduction is performed according to the planned spatial reduction path. The results show that when the muscles are stretched the same stretch length, the strain of the gluteus medius is the largest. It is most prone to deformation under and the muscle injury is most easily to occur. During the pelvic fracture reduction, the strain of gluteus maximus is the largest, and it is most prone to deformation and injury. The traction length is the largest, and the traction force mainly comes from the gluteus maximus. This study provides reference for the robot assisted pelvic fracture reduction.